HUBUNGAN PEMBERIAN MAKANAN TAMBAHAN DENGAN KENAIKAN BERAT BADAN BALITA GIZI KURANG DI KEC. KEDAMAIAN KOTA BANDAR LAMPUNG TAHUN 2021 - Mariyani, Tuti; Nurhartanto, Adhi (NHM PRESS, 2024)
Indonesia's most important capital for intelligent human resources, productive, especially healthy to support the country's developmentsuccess. The nutritional disorders case of pregnant women, infants and toddlers is a problem that must be handled seriously. The purpose of study was to find out the relationship between supplementary feeding and weight gain of undernourished toddlers in the District of Peace, Bandar Lampung City in 2021. This study used a quasi-experimental design in a one group before and after design on the target of undernourished toddlers with an intervention in the form of supplementary feeding. In this study, the population was all undernourished children under five in the Peace District, the working area of ​​the Satellite Inpatient Health Center who received additional biscuits in June 2021 as many as 31 children. Data were collected through interviews, observation and weighing. The results of the study after PMT showed that 19 (61.3%) underweight children under five experienced weight gain. 17 toddlers consume PMT well, and 14 toddlers consume PMT not well. The results of the statistical test analysis using the Chi-square method obtained a p value of 0.000 at alpha = 0.05, meaning that the relationship was in the provision of additional food with weight gain for undernourished children under five in the Peace District of Bandar Lampung City in 2021.